Health Activism Is the New Black: The Communication by Non-Governmental Organizations about COVID-19 - Célia Belim (Romanian Journal of Communications and Public Relations)
This article focuses on understanding how non-governmental organizations (NGOs), in their role as health activists, have built their communication on COVID-19. Atriple analysis is used, qualitative thematic, rhetorical, and semiotic, applied to a corpus of advertisements (n=68). The findings show that, thematically, NGOs propose an agenda that includes prevention, awareness (e.g., COVID 19’s impact, aid, violence, disinformation, (ir)responsibility), donation, and praise for altruism. Rhetorically, ethos is built through the emphasis on the credibility of NGOs, the elite figures and the authenticity and factualism of human faces. Capitalizing on the innate emotional nature of humans, pathos is entangled in a plurality of positive (e.g., love, pride, hope) and negative emotions (e.g., worry). A variety of logos based rhetorical strategies are employed, particularly those grounded in evidence, such as the use of statistical data, factual references, and pedagogical descriptions intended to clarify and support the argument. Additionally, the text incorporates a range of persuasive and emotional tactics, including stylistic features, phatic elements (e.g., questions designed to initiate contact with the audience), motivational language, and associations with noble causes. Techniques such as personalization and humanization are used to foster authenticity and public identification, alongside the portrayal of victims to evoke empathy. Furthermore, the symbolic use of icons and plastic signifiers, including colour schemes, enhances the communicative and emotional appeal of the message. The article offers professional, social, and scientific contributions.